VIRTUAL MADNESS, CULTURAL REALITIES: A CRITICAL CROSSED EXAMINATION OF PSYCHOSIS REPRESENTATION IN LAYERS OF FEAR AND HELLBLADE SENUA’S SACRIFICE AND THEIR RECEPTION IN ONLINE COMMUNITIES - Rebecchi, Kevin; Vial, Elisa (Brazilian Creative Industries Journal, 2025)
This article presents a thorough and comparative analysis of two video games, Layers of Fear (LOF) and Hellblade: Senua’s Sacrifice (HSS), exploring their representations of madness. By combining an examination of relevant scientific literature with an analysis of Steam and Reddit forums, the study provides a comprehensive overview of gamer reactions and the ethical implications of developers’ representation choices. While LOF takes a horror-oriented approach, eliciting mixed reactions, HSS stands out for its nuanced conceptualization resulting from collaboration with experts and individuals living with psychoses. The article underscores the importance of sensitivity, respect, and empathy toward psychosis in gaming representation, highlighting the diversity of approaches in addressing mental health through video games. Additionally, the discussion delves into fundamental questions regarding artistic versus realistic representation of madness, challenging norms and emphasizing the poetic power of video games as a medium for artistic expression and understanding of the psychotic experience.